2023
DOI: 10.1021/acs.inorgchem.2c03193
|View full text |Cite
|
Sign up to set email alerts
|

Isocyanide Ligands Promote Ligand-to-Metal Charge Transfer Excited States in a Rhenium(II) Complex

Abstract: A metal-to-ligand charge transfer with mixed intraligand character is observed for the rhenium hexakisarylisocyanide complex [Re(CNAr)6]PF6 (CNAr = 2,6-dimethylphenylisocyanide, λmax = 300 nm). Upon oxidation to [Re(CNAr)6](PF6)2, the dominant low energy optical transition is a ligand-to-metal charge transfer (LMCT) mixed with intraligand transitions (λmax = 650 nm). TD-DFT was used to identify the participating ligand-based orbitals in the LMCT transition, revealing that the majority of the donor orbital is b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 36 publications
(84 reference statements)
1
9
0
Order By: Relevance
“…The vibrational fine structure known for this complex is not conveyed within its calculated absorption spectra as only electronic excitations were calculated. Interestingly, both low energy transitions exhibit 99% LMCT character, uncharacteristic of previously reported rhenium­(II) complexes where metal–ligand mixing is more prevalent. , Solvatochromism was similarly not observed for this complex across four solvents (dielectric constants ranging from 1.8–8.9), further supporting the presence of highly symmetric LMCT excited states (Figures S5 and S6). …”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The vibrational fine structure known for this complex is not conveyed within its calculated absorption spectra as only electronic excitations were calculated. Interestingly, both low energy transitions exhibit 99% LMCT character, uncharacteristic of previously reported rhenium­(II) complexes where metal–ligand mixing is more prevalent. , Solvatochromism was similarly not observed for this complex across four solvents (dielectric constants ranging from 1.8–8.9), further supporting the presence of highly symmetric LMCT excited states (Figures S5 and S6). …”
Section: Resultssupporting
confidence: 81%
“…Interestingly, both low energy transitions exhibit 99% LMCT character, uncharacteristic of previously reported rhenium(II) complexes where metal−ligand mixing is more prevalent. 51,52 Solvatochromism was similarly not observed for this complex across four solvents (dielectric constants ranging from 1.8−8.9), 53−55 further supporting the presence of highly symmetric LMCT excited states (Figures S5 and S6). 52 The optical transitions that dominate the UV−vis absorption spectrum of MnCp* 2 are similar to those quantified for ReCp* 2 (Figure 5A).…”
Section: ■ Introductionmentioning
confidence: 73%
“…The increased energy is predominantly the result of the increased effective nuclear charge felt at the location of the relevant d-orbitals for manganese­(I) relative to that of chromium(0), resulting in a significant stabilization of the π­(d) orbitals (π­(d xy ), π­(d xz ), π­(d yz ) in Figure b; equivalent to t 2g in Figure a). The assignment of mixed IL/MLCT character of [Mn] + for the lowest-lying transition agrees with related studies on manganese­(I) hexakis­(arylisocyanide) complexes. ,,, Furthermore, prior computational studies on tungsten(0) and rhenium­(I) arylisocyanides have likewise shown that enhanced extinction coefficients can result from the lowest transition having mixed MLCT and π–π* (CN–C) character. , …”
Section: Resultsmentioning
confidence: 88%
“…36,47,49,55 Furthermore, prior computational studies on tungsten(0) and rhenium(I) arylisocyanides have likewise shown that enhanced extinction coefficients can result from the lowest transition having mixed MLCT and π−π* (C�N−C) character. 40,63 The UV−vis absorption spectra of [Cr], [Mn] + , and [Fe] 2+ (Figure 3) all display an intense band centered at 350 nm originating primarily from 1 π−π* transitions involving pyrene moieties, as also seen in the free L Pyr ligand (Table 2). At shorter wavelengths, 1 π−π* transitions from the m-terphenyl backbone of the isocyanide ligands appear.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It also further underscores the opportunity to leverage TD-DFT to help identify and visualize the ligand-based orbitals that participate in LMCT transitions, and gain a deeper understanding of the ligand properties needed to support low energy LMCT excited states. 22,47,55,63–65…”
Section: Designing Transition Metal Complexes With Low-lying Lmct Exc...mentioning
confidence: 99%